Impact of level of neonatal care on phlebotomy and blood transfusion in extremely low birthweight infants: a prospective, multicenter, observational study - Kitsommart, Ratchada; Limrungsikul, Anchalee; Tongsawang, Numtip; Thamwiriyakul, Nirucha; Deesomchok, Areeya; Pithakton, Nuttanan; Paes, Bosco (Frontiers in Pediatrics, 2023)
Objectives: To explore the level of neonatal care on cumulative phlebotomy loss (cPL) and red cell transfusions in extremely low birthweight (ELBW; birthweight (BW) <1000g) infants, up to 40 weeks post-conceptual age (PCA). The secondary objective was to determine the associations between cPL and number of transfusions and between transfusions and hospital outcomes. Methods: A prospective, comparative, observational study was conducted in two level IV and two level III neonatal intensive care units (NICUs) in Thailand. Daily cPL volume and number of blood tests were recorded. Descriptive data are reported as frequency and percentage for categorical variables and median [25th percentile (P25), 75th percentile (P75)] for continuous data according to the data distribution. A p-value<0.05 was considered statistically significant. Results: 210 ELBW infants were included; 99 and 111 were admitted to level IV and level III NICUs, respectively. Birth weight of level IV infants was lower 780.0 [660.0, 875.0] vs. 865.0 [723.0, 930.0]g; p <0.001]. Initial group hematocrits were similar (43.1% vs. 44.0%, p= 0.47). cPL for each infant was 28.1 [16.5, 46.4] mL. Level IV infants had more tests (n= 89 [54, 195] vs. 59 [37, 88], p<0.001). Counterintuitively, there was a lower cPL trend in level IV infants, but this was insignificant (19.6 [12.3, 52.3] vs. 28.9 [19.3, 45.3] mL; p =0.06). The number of transfusions in both NICUs was similar 4 [2, 6], with a strong correlation between cPL and number of transfusions (r = 0.79, p <0.001). Transfusions were significantly associated with bronchopulmonary dysplasia [BPD; adjusted RR (95%CI, 2.6 (1.2, 5.3), p =0.01]. Conclusions: Level IV NICUs conducted more blood tests in ELBW infants without a difference in cPL, and number of transfusions. Cumulative PL correlated with number of transfusions and was associated with BPD risk. Minimizing cPL by point-of-care tests and restrictive transfusion criteria, may reduce need for transfusion.